Shrimp spoilage mechanisms and functional films/coatings used to maintain and monitor its quality during storage - Lin, Duanquan; Sun, Le-Chang; Chen, Yu-Lei; Liu, Guang-Ming; Miao, Song; Cao, Min-Jie (Trends in food science & technology, 2022)
The quality change of shrimp is inevitable during storage, while shrimp preservation is extremely important in the fishery and food industries. Many efforts have been devoted to explore preservation strategies to maintain shrimp quality and develop sensitive freshness indicators to monitor shrimp quality during storage in the last decade. This review provides an update on the current knowledge of the mechanisms of shrimp quality changes, active films/coatings used to maintain shrimp quality, and smart films used to indicate the shrimp freshness during low-temperature storage. The enzymatic activities of trypsin-like protease, cathepsin B, polyphenoloxidase, prophenoloxidase, and ATPase play important roles in protein hydrolysis, formation of melanin and degradation of ATP in shrimp, resulting in muscle softening, melanosis and loss of umami. More importantly, the microbial activity is the main reason for forming off-flavor in shrimp during low-temperature storage. In addition, lipid and protein oxidation, astaxanthin degradation and cell wall damage caused by ice crystals during frozen storage can also contribute to the quality changes of shrimp. The use of active coatings/films is an effective method to maintain the shrimp quality during storage, because the encapsulated functional compounds (e.g., protein hydrolysates, essential oil and plant extracts) can act as anti-melanosis, antibacterial and antioxidant agents. In addition, smart pH-responsive films, as a simple and effective technique to monitor the quality changes of shrimp, have received increased interest in recent years, and natural pigments (e.g., anthocyanin) can be used as freshness sensors in such films to enhance its convenience for application.